Leadership Strategies of Private Middle School Principals in Enhancing Teacher Performance at Darul Amin - Wahyuni, Sri; Rifa'i, Muhammad; Rohman, Fatkhur (IKIP PGRI Bojonegoro, 2024)
The quality of Islamic boarding school education occurs organically with the figures of kiai, ustadz and Islamic boarding school managers implementing an internal quality assurance system for the implementation of Islamic boarding school education. The provision of education in Islamic boarding schools is adequate, programmed and planned. Even now, education in Islamic boarding schools still exists and is consistent as a center for teaching religious sciences. The purpose of this research is to determine the synergy of the committee and the school principal in providing Islamic education which can provide added value in the form of knowledge, morals, charity or its application in everyday life and is beneficial for the students. This research includes field research using qualitative methods. The aim is to determine the synergy and quality of leaders in managing educational institutions.